Analisis Kepatuhan Wajib Pajak UMKM atas Pemberlakuan PP 23 2018 dibandingkan dengan PP 46 2013 (Studi Kasus UMKM Binaan ZAF Internasional) - Djuhartono, Tjipto; Utami, Ai Annisaa; Zahrudin, Zahrudin (Sosio e-Kons, 2019)
The government has been working synergistically lately to encourage tax revenue from the MSME sector by issuing various tax regulations that are pro to MSME needs, including by issuing PP number 23 of 2018. This PP is a revision of the previous PP issuance namely PP number 46 of 2013 with an original tariff of 1% of the value. The research aims to reveal tax compliance with the changes in government regulations conducted by the SMEs in the City of Depok, which is a ZAF International-guided SMEs. The research method uses a survey of MSMEs in Depok City. The sampling technique in this study uses purposive sampling for the UMKM Depok region and is under the auspices of ZAF International. The data analysis method uses FGD with a qualitative approach, the results of this study indicate that the level of compliance of ZAF-assisted MSMEs before and after the enactment of PP 23 of 2018 is getting better and increasing because it is driven by a socialization program carried out by the government.